Recent cancer treatment and memory decline in older adults: An analysis of the 2002–2012 Health and Retirement Study. Issue 3 (May 2018) - Zuniga, Krystle E.; Bishop, Nicholas J.
Abstract: Objective : Few studies have examined the impact of cancer treatment on cognitive trajectories in the growing population of older adults diagnosed with and surviving cancer. This study examined whether recent cancer and its treatment accelerated memory decline in older adults. Materials and Methods : We conducted a secondary analysis of observations drawn from the Health and Retirement Study (2002–2012), a population-based sample of older adults in the United States. Changes in immediate (IWR) and delayed word recall (DWR) scores were estimated by latent growth modeling in individuals who never had cancer ( n  = 10, 939) or had been diagnosed with cancer between 2000 and 2002 and received treatment with some combination of radiation and/or surgery ( n  = 240), chemotherapy only ( n  = 34), or chemotherapy and some combination of radiation and/or surgery ( n  = 64). Results : In the period immediately following treatment, individuals reporting a recent cancer treated with chemotherapy and surgery/radiation experienced significantly more rapid decline in IWR ( b = − 0.34, SE = 0.17, p  = 0.047) and DWR ( b  = − 0.38, SE  = 0.19, p  = 0.049) than the non-cancer group. Sensitivity analyses addressing mortality selection and memory-related disease at baseline attenuated the strength of these associations. There were no other statistically significant differences in estimated linear or quadratic slope by cancer status or treatment. Conclusion : Our results support a potential association between recent cancer treatment and trajectories of memory decline in older adults and provide guidance on the interpretation of statistical estimates from panel studies of health and aging.